2013
DOI: 10.1002/mc.21975
|View full text |Cite
|
Sign up to set email alerts
|

Stable expression of human VDR in murine VDR-null cells recapitulates vitamin D mediated anti-cancer signaling

Abstract: Mammary tumor cells derived from vitamin D receptor (VDR) knock-out (KO) mice were engineered to stably express wild-type (WT) or mutated VDR for characterization of the mechanisms by which 1,25-dihydroxyvitamin D (1,25D), the VDR ligand, mediates growth regulation. Although KO cells were completely resistant to 1,25D, introduction of WT human VDR restored gene expression and growth inhibition in response to 1,25D and a variety of structural analogs. Pdgfb, Vegfa, and Nfkbi were identified as genomic targets o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…For the studies described here, WT145 and KO240 cells were adapted to growth in DMEM/F12 medium supplemented with 5% charcoal-stripped FBS to eliminate exposure to serum vitamin D metabolites. In previous work [14] we confirmed that stable expression of hVDR into KO240 cells using a plasmid vector (pSG5-hVDR-hygro) recapitulated 1,25D mediated anti-cancer signaling, however, sensitivity to 1,25D was lost over time in these clones. To overcome this problem, we created a retroviral hVDR vector (pBABE-puro-hVDR, Fig 1) and generated a new series of hVDR expressing cells which we characterized in the present studies.…”
Section: Methodssupporting
confidence: 79%
See 1 more Smart Citation
“…For the studies described here, WT145 and KO240 cells were adapted to growth in DMEM/F12 medium supplemented with 5% charcoal-stripped FBS to eliminate exposure to serum vitamin D metabolites. In previous work [14] we confirmed that stable expression of hVDR into KO240 cells using a plasmid vector (pSG5-hVDR-hygro) recapitulated 1,25D mediated anti-cancer signaling, however, sensitivity to 1,25D was lost over time in these clones. To overcome this problem, we created a retroviral hVDR vector (pBABE-puro-hVDR, Fig 1) and generated a new series of hVDR expressing cells which we characterized in the present studies.…”
Section: Methodssupporting
confidence: 79%
“…Recently we provided proof of principle that expression of VDR in KO240 cells using a plasmid vector recapitulated 1,25D mediated anti-cancer signaling [14] however, these VDR expressing cells lost sensitivity over time. For these follow-up studies, we created a retroviral hVDR expression vector (pBABE-hVDR-Puro, Fig 1A) and selected multiple KO240 clonal cell lines with stable expression of hVDR protein.…”
Section: Resultsmentioning
confidence: 99%
“…There are no known interactions for the other compounds, except selenium, which inhibits growth in some cases while inducing it in others [356] , [357] . In a related characteristic of cancer cells, evasion of antigrowth signaling, all compounds are able to inhibit growth except vitamin B, which shows no relationship, and carotenoids, which have mixed results [255] , [358] , [359] , [360] , [361] , [362] , [363] , [364] , [365] , [366] . Similarly, all of the compounds are able to prevent replicative immortality by impairing telomerase activity or inducing senescence [364] , [367] , [368] , [369] , [370] , [371] , [372] , [373] , [374] , [375] , [376] and increasing cell death except for vitamin B, which has no known relationship to apoptosis [377] , [378] , [379] , [380] , [381] , [382] .…”
Section: Complementary Effects On the Enabling Characteristics Of Canmentioning
confidence: 99%
“…Conversely, downregulation of VDR expression in ALVA-31 prostate cancer cells attenuated the ability of 1,25D to inhibit cell growth (47). Keith et al (48) argued that the percentage of VDR-positive cells rather than the absolute level of cellular VDR expression in a heterogenous tumor would be the best predictor of growth inhibition induced by vitamin D compounds. Overall, these studies demonstrated that VDR is required for the antiproliferative effect of 1,25D in cancer cells.…”
Section: The Role Of Vdr In Cancermentioning
confidence: 99%